Pemasaran UMKM Berbasis Teknologi di Kelurahan Sompe Kecamatan Sabbangparu Kabupaten Wajo - Agus Purwanto; Andi Sumangelipu; Suharjum; Andi Besse Nurul Adha (Compile Journal of Society Service, 2024)
Sompe Village is one of the villages in Sabbangparu Subdistrict, Wajo Regency, which has a diverse occupational landscape comprising civil servants, entrepreneurs and farmers. However, the majority of the population are engaged in agricultural and entrepreneurial activities. In general, farmers and entrepreneurs continue to utilise conventional methods for the marketing of their business and agricultural products, which has resulted in limited productivity and reach in this regard. It is therefore recommended that this community service research should include a counselling component, which introduces technology-based or digital MSME-based marketing methods. The objective is to enhance productivity and expand the reach of the community's business and agricultural products marketing network, thereby increasing their income sources.